The Role of Communication Methods in Changing the Values of the Urban Family - مرعب ماهر فرحان (ALBAHITH ALALAMI, 2015)
This article discusses the change of values in urban family, because of various communication media and modern technologies as one of the most important factors affecting the changing family values in urban areas, this means becoming part of urban life. And focuses on the family in urban areas, for the privacy of the social, economic, demographic and cultural help to this effect, and because cities are the most friction and interaction with modern technologies.